A Comparative Study of Creativity among Boys and Girls of Class VII - Siddiqi, Saima (INDIAN EDUCATIONAL REVIEW, 2011)
The purpose of this study was to investigate differences for boys and girls in terms of the relation between different aspects of creativity. A sample of 50 boys and 50 girls’ studying in two secondary schools of Aligarh city was randomly selected. The investigator had personally met the participants and administered the tool. Torrance Test of Creative thinking (Verbal Form A) designed by E. P. Torrance (1968) was used. Mean S.D.S and T-test were calculated to analyse the data. The findings reveal that boys do not differ significantly in all the variables of verbal creativity, except the measures of originality from the girls.